Knowledge of SARS-CoV-2 antigen detection and proper use of rapid diagnostic self-test among Shanghai residents in China - Gu, Ren-Ping; Zhu, Ai-Yong (Frontiers in Public Health, 2023)
Objectives To assess and evaluate the knowledge of Shanghai, China, residents on the use of SARS-CoV-2 antigen detection and rapid diagnostic self-test. Methods A cross-sectional electronic survey using a self-administered questionnaire was sent via the online platform, Sojump, to general individuals. Multiple linear regression analysis was performed to determine the variables associated with knowledge of self-test. Results A total of 283 participants were recruited between July 1, 2022 and July 20, 2022 through an online survey. The mean score of knowledge on the tests was 14.33 ± 2.85 (out of 21). The questions concerning the depth of swab insertion and minimum number of swab rotations in the nostril, necessity of bilateral sampling, necessity of rotating and squeezing the swab for 10 times in the extraction buffer tube, and waiting time for the results showed the highest rate of incorrect responses. In the multiple regression analysis model, sex, social status, and source of information were associated with the knowledge on the self-test kits. Conclusion Immediate health education programs should be made available and the kits could be improved appropriately to ensure adequate knowledge. The use of technology should be fully leveraged to achieve accurate self-diagnosis and correct interpretation of the results.